2010
DOI: 10.1186/1471-230x-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Short versus standard treatment with pegylated interferon alfa-2A plus ribavirin in patients with hepatitis C virus genotype 2 or 3: the cleo trial

Abstract: BackgroundIn patients with chronic hepatitis C virus (HCV) genotype 2 or 3, 24 weeks' treatment with pegylated interferon alfa (PEG-IFN-alpha) and ribavirin induces a sustained virological response (SVR) in almost 80% of cases. Evidence suggests that a similar response rate may be obtained with shorter treatment periods, especially in patients with a rapid virological response (RVR). The aim of this study was to compare the efficacy of 12 or 24 weeks of treatment in patients with chronic HCV genotype 2 or 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
2
23
2
2
Order By: Relevance
“…However, some studies have shown that higher ALT levels are predictors of SVR [41]. Viral factors affecting treatment outcome include HCV RNA titers at baseline, with lower levels showing increased probability of SVR [22,31,41]. However, no difference in the SVR was observed in patients with high viral load compared to low viral load in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…However, some studies have shown that higher ALT levels are predictors of SVR [41]. Viral factors affecting treatment outcome include HCV RNA titers at baseline, with lower levels showing increased probability of SVR [22,31,41]. However, no difference in the SVR was observed in patients with high viral load compared to low viral load in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, patients with higher BMI were found to have a lower chance of achieving SVR (Table 2). However, no relationship between BMI and SVR was shown in some previous studies on hepatitis C [22,25,34]. Large trials of HCV patients with bridging fibrosis or cirrhosis have shown that PEG-IFN and RBV combination therapy achieves SVR rates of 43-44% [11,16].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations